Establishing nitrogen-efficient wheat production systems in the Indo-Gangetic Plains through the deployment of BNI technology - Tobita, Satoshi; Yoshihashi, Tadashi; Kishii, Masahiro; Subbarao, Guntur Venkata; Joshi, Arun Kumar (Springer Singapore, 2025)
Because of the rapid nitrification process in soil, more than half of the applied nitrogen fertilizer is not utilized by crops and is lost to the environment, which resulted in low nitrogen-use efficiency (NUE) in agricultural production systems. Suppression of nitrification is key to improving NUE, allowing for more N to stay in the soil and to be used by crops. Biological nitrification inhibition (BNI) is a function of plants that suppresses the nitrification process using special chemical compounds—biological nitrification inhibitors (BNIs)—from the roots, which block key enzymes involved in the nitrification process. For wheat, one of the most fertilized crops in the world, its wild relative Leymus racemosus was found to have a high BNI capacity. The trait was successfully transferred into international wheat varieties, such as Munal and Roelf. The BNI-enabled varieties/lines have been proven to suppress nitrification and utilize soil nitrogen more efficiently than the original varieties. The SATREPS project, “Establishment of nitrogen-efficient wheat production systems in Indo-Gangetic Plains by the deployment of BNI-technology,” was started in 2022 for the social implementation of these BNI-enabled wheat lines in the Indo-Gangetic Plains (IGPs), a food basket for 1.4 billion people, where farmers apply extremely high rates of N fertilizer to wheat. The project aims at proposing of the new nitrogen-efficient wheat production systems using BNI technology and demonstrating in farmers field that no decrease in grain production nor quality under 30% less of N fertilizer application with BNI technology. As the deployment of BNI technology in the IGPs will be achieved by having an Indian elite wheat variety with enhanced BNI capacity. The project advances breeding efforts to transfer the BNI ability from BNI-enabled international wheat varieties to Indian elite varieties. A molecular marker of the alien chromosome segment (Lr#n-SA), conferring the BNI traits, was developed in the current project, and the marker is used to select for enhanced BNI capacity. To demonstrate the environmental benefits of BNI traits in fields, the following methodologies were tried: (1) collecting N2O gas emitted from the rhizosphere and (2) collecting soil water at different depths to investigate the dynamics of N, especially NO3-N, in the soil. After verification, the two methods will be applied in experimental fields in the IGPs to monitor and compare the emission of N2O and the emergence of NO3-N in BNI-enabled field with non-BNI field.